RECOMMENDATIONS TO CONTROL ASTHMA DURING PREGNANCY - E.A. Vishneva; L.S. Namazova; I.A. Gromov (Педиатрическая фармакология, 2008)
This article touches upon the most topical problem of the modern medicine — treating pregnant patients, particularly those suffering from bronchial asthma and allergic rhinitis. Based on a number of case studies, the authors argue the need for the continuation of treatment during pregnancy in order to gain and maintain control over the diseases. The risk of complications and their range are significantly higher in case of non controlled course of bronchial asthma vs. that under an adequate  therapy. The article gives the basic provisions to treat the said category of patients.Key words: bronchial asthma, allergic rhinitis, treatment, risk factors, pregnancy.